2022
DOI: 10.3390/antiox11020337
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compounds and Antioxidant Capacity of Sea Cucumber (Cucumaria frondosa) Processing Discards as Affected by High-Pressure Processing (HPP)

Abstract: Sea cucumber processing discards, which include mainly internal organs, represent up to 50% of the sea cucumber biomass, and are a rich source of bioactive compounds, including phenolics. This work aimed to extract free, esterified, and insoluble-bound phenolics from the internal organs of the Atlantic sea cucumber (C. frondosa) using high-pressure processing (HPP) pre-treatment. The sea cucumber internal organs were subjected to HPP (6000 bar for 10 min), followed by the extraction and characterization of phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 43 publications
0
22
0
Order By: Relevance
“…Pre-treatments also affect the content of sea cucumber phenolic and their antioxidant activities. For example, free, esterified, and insoluble-bound phenolics from the body wall and internal organs of Atlantic sea cucumber ( Cucumaria frondosa ) were determined using high-pressure processing (HPP) pre-treatment [ 5 , 24 ]. Results demonstrated that HPP significantly improved the TPC, TFC, and antioxidant activity.…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
See 2 more Smart Citations
“…Pre-treatments also affect the content of sea cucumber phenolic and their antioxidant activities. For example, free, esterified, and insoluble-bound phenolics from the body wall and internal organs of Atlantic sea cucumber ( Cucumaria frondosa ) were determined using high-pressure processing (HPP) pre-treatment [ 5 , 24 ]. Results demonstrated that HPP significantly improved the TPC, TFC, and antioxidant activity.…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
“…They suggested that phenolic extracts which were rich in epicatechin and 2,5-dihydroxybenzoic acid might inhibit the growth of cancer cells and induce apoptosis in A549 (human non-small lung carcinoma) and HeLa (cervix adenocarcinoma) cells. However, the phenolic compounds of the Atlantic sea cucumber’s ( C. frondosa ) body wall and internal organs were used in various in vitro biological assays [ 5 , 24 ]. Results suggested that phenolic compounds had the potential to inhibit DNA oxidation, low-density lipoprotein (LDL) oxidation, formation of advanced glycation end products (AGEs), and α-glucosidase and tyrosinase enzymes.…”
Section: Bioactive Compounds Of Sea Cucumbers and Their Antioxidant A...mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, p -hydroxycinnamic acid is derived from tyrosine with the assistance of tyrosine ammonia-lyase (TAL), whereas trans cinnamic acid is derived from phenylalanine, catalyzing by phenylalanine ammonia-lyase (PAL). The major phenolics present in plants are flavonoids, phenolic acids, tannins, stilbenes, lignans, and coumarin [ 26 , 27 , 28 ]. Phenolic compounds are well known as antioxidants, which demonstrate inhibitory activities against α-glucosidase and tyrosinase activities as well as LDL-cholesterol, DNA, and lipid oxidation [ 29 ].…”
Section: Bioactive Compounds Of Plmentioning
confidence: 99%
“…It is mainly fished for its internal muscle bands and body wall [ 10 , 12 ]. All the other remaining tissues including aquapharyngeal bulb (flower) and internal organs such as digestive tract, gonads, and respiratory tree are discarded as processing waste [ 11 , 12 , 13 ]. A limited number of studies have reported the potential of utilizing the Atlantic Sea cucumber by-products as precursor materials for bioactive peptides [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%